Post-traumatic stress, anxiety, and depressive symptoms in caregivers of children tested for COVID-19 in the acute phase of the Italian outbreak. (March 2021) - Orsini, A.; Corsi, M.; Pedrinelli, V.; Santangelo, A.; Bertelloni, C.; Dell'Oste, V.; Cordelli, D.; Perrone, A.; Parini, L.; Lanari, M.; Massimetti, G.; Bonuccelli, A.; et al.
Abstract: Background: The recent COVID-19 pandemic pointed out new burdens for researchers on mental health and that evidence-based (EB) studies on vulnerable populations are timely needed. The present paper aims at analysing the impact of suspicious of SARS-COV-2 infection in a cohort of parents presented at 3 major hospitals (spread between north and center of Italy) during the Italian COVID-19 pandemic phase 1. Methods: Participants of the present cross-sectional, multicenter study were parental couples of children suspected to have COVID-19 who underwent testing with nasopharyngeal swabbing. All subjects were assessed by means of the: Impact of Event Scale-Revised (IES-R), Generalized Anxiety Disorder 7-Item (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) in order to evaluate Post-traumatic stress (PTSS), anxiety, and depressive symptoms, respectively. Outcomes: Results evidenced that parents whose children tested positive for COVID-19 were more prone to developing PTSS, anxiety and depressive symptoms. The same results emerged for parents who had quarantined as opposed to those who had not. Moreover, patients who suffered economic damage showed a higher prevalence of anxiety and depressive symptoms, whereas PTSS was more common among unemployed subjects and among mothers. Interpretation: This study identified a mental health strain represented by parenting a child who tested positive for SARS-CoV-2 infection. Further EB research is needed to develop evidence-driven strategies to reduce adverse psychological impacts and related psychiatric symptoms in caregivers of COVID-19 infected children during the next phases of the pandemic.